CORRELATION BETWEEN CHILD PUGH SCORE AND CYSTATIN C IN LIVER CIRRHOSIS PATIENTS - Deshinta Putri Mulya; Siti Nurdjanah; Neneng Ratnasari (Acta Interna The Journal of Internal Medicine, 2011)
ABSTRACTBackground. Renal dysfunction is a serious problem and it provides a poor prognosis for patients with advanced liver cirrhosis, where this condition can progress to kidney failure. This condition is known as hepatorenal syndrome. Cystatin C utilization as a marker of decreased kidney function in patients with liver cirrhosis has been widely proven. Data on how far the severity of liver cirrhosis can affect the decline in renal function has not been widely known. Objective. This study aimed is to verify correlation between the severity degree of the liver (Child Pugh/CP score) with levels of Cystatin C serum. Methods. This study was a cross sectional study. Population studied were patients with liver cirrhosis who visited the clinic of Gastroentero-hepatology and treated in the department of Internal Medicine ward Dr. Sardjito Hospital - Yogyakarta during October 2009 - March 2010. Data were analyzed with a computer; the analyzed of the CP score correlation with increased levels of Cystatin C using Spearman correlation for data not normally distributed. Result. We found 48 research subjects during the month of October 2009 - March 2010. The subjects were 35 male (72.9%) and 13 female (27.1%) with average age 53.1 ± 11.9 years old. Subjects with CP-A were 9 patients (18.8%), CP-B were 14 patients (29.2%) and CP-C were 25 patients (52.1%). The range value of Cystatin C between CP class shows CP-A  0.7 - 0.97 mg/L, CP-B 0.7 - 0.49 mg/L, and CP-C 0.7 – 2.49 mg/L (statistically significant difference with p <0.05). Liver cirrhosis patients who had Cystatin C levels <0.96 mg/L were 22 patients (45.83%) and 26 patients (54.1%), had higher levels of Cystatin C> 0.96 mg/L. Child score was positively correlated to increased levels of Cystatin C (p= 0.000; r= 0.566) linear regression equation with Cystatin was = 0.37 + 0.08 * Child score (r square 0.32). Conclusion. This study concluded that the Child score had a moderate positive correlation with Cystatin C serum level.  Key words: Liver Cirrhosis – Child Pugh score - Cystatin C